Assessment of Vitamin D level in Depression and its association with severity of depression (Journal of Psychiatrists' Association of Nepal, 2025)
Background: Depression is a mental health condition which in severe conditions may lead to suicide and increase risk of mortality. Some biological markers have been identified as reliable indicators of depression. The aim of this study was to assess the level of depression in treatment naïve patients and compare the level of Vitamin D among treatment naïve cases of depression.Methods: The study was a cross-sectional single hospital-based study conducted in treatment naïve patients diagnosed as depression by consultant psychiatrist as per ICD-10 in inpatient and outpatient department of Psychiatry, Patan Academy of Health Sciences, Lagankhel, from March 2021 to March 2022. 55 samples (treatment naïve cases of depression) were selected purposively. Information on age and gender were collected in the proforma and Serum Vitamin D level was also measured. Descriptive and inferential analysis was done using EZR software.Results: 40% of the patients had moderate depression, 32.7% had mild depression and 27.3% had severe depression. 58.2% had optimal serum Vitamin D level, 25.4% had insufficient and 16.4% had deficient Vitamin D level. A significant association (p